Stable Isotope Sourcing of Wool from Textiles at Pacatnamú. (18th January 2018) - Szpak, P.; Millaire, J.‐F.; White, C. D.; Donnan, C. B.; Longstaffe, F. J.
Abstract : Stable carbon and nitrogen isotopic compositions were determined for wool textiles from the Lambayeque ( c . ad 1100–1320) occupation at Pacatnamú in the Jequetepeque Valley, northern Peru. The isotopic data demonstrate that the wool was not obtained via long‐distance exchange with the highlands and was most probably derived from locally raised camelids. In light of other lines of evidence (diversity of dyes used to produce the same colours in textiles and the low quality of the weaving), textiles at Pacatnamú appear not to have been as effective a marker of political power and prestige for local elites as they were elsewhere in the Andean region.